Experiencing local culture and learning english A new concept for a tour package in Kampung Batik Cibuluh, Bogor - Sari Rejeki; Erol Kurniawan; Anindia Ayu Rahmawati; Najwa Amira; Rasya Annisa Anom; Shelvi Fitria Azizah (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Kampung Batik Cibuluh, recognized by the Ministry of Tourism and Creative Economy as a tourism village in Bogor, has become a growing attraction for sustainable tourism that offers educational experiences. This destination not only provides hands-on batik-making but also cultural and educational tours immersing visitors in local culture, including the history, philosophy, and processes of batik production. One key challenge is the lack of structured programs, with no prior study managing or developing tour packages for Kampung Batik Cibuluh. To address this issue, one effective solution is a tour package that integrates local culture, sustainable tourism practices, and English language learning. Combining local culture and language learning in tour packages represents an innovative approach. The results are expected to preserve and promote local culture, enhance sustainable tourism, and offer local and international tourists opportunities to learn a foreign language. Ultimately, this study equips Kampung Batik Cibuluh with effective strategies to compete with other destinations